Controlling magnetoelectric coupling effect of CoFe2O4–Ba0.8Sr0.2TiO3 multiferroic fluids by viscosity. (1st February 2023) - Wu, Heng; Zhang, Yulin; Ao, Hong; Zhong, Siqi; Zeng, Zhixin; Li, Wenchuan; Gao, Rongli; Fu, Chunlin; Chen, Gang; Deng, Xiaoling; Wang, Zhenhua; Lei, Xiang; et al.
Abstract : The multiferroic fluids has an obvious magnetodielectric effects, and presents large magnetoelectric coupling coefficient of 89.8 V (cm Oe) −1 . Abstract : Multiferroic materials have garnered significant attention in recent years due to their unique magnetoelectric coupling effect. However, it is difficult to directly switch the magnetization/polarization directions of conventional solid multiferroic materials under the action of an applied electric/magnetic field, limiting the enhancement of the magnetoelectric coupling coefficient. In this study, CoFe2 O4 (CFO) nanoparticles with an average size of 52.27 nm were prepared using the chemical co-precipitation method, and Ba0.8 Sr0.2 TiO3 (BST) nanoparticles with an average size of 66.10 nm were prepared via the sol–gel method. On this basis, CFO–BST multiferroic fluids were created through ball milling, and the effect of viscosity on the magnetoelectric properties was investigated. It was found that viscosity is positively correlated with the settling stability of the fluids. With increasing viscous resistance and stability, the magnetic dielectric response of the multiferroic fluids increases at first and then decreases. The highest magnetic dielectric response (3.9%) was observed for fluids with a viscosity of 1000 mPa s. Furthermore, it was discovered that the multiferroic fluids exhibited an obvious switching effect when subjected to a discontinuous magnetic field. Additionally, the polarization intensity of the multiferroic fluids was found to increase initially before decreasing with increasing viscosity. The multiferroic fluids with a viscosity of 1000 mPa s achieved a magnetoelectric coupling coefficient of 89.8 V (cm Oe) −1 when subjected to an applied magnetic field of 91 Oe due to their good stability and suitable viscosity. This investigation implies that multiferroic liquids may have potential application in information storage and new capacitors.